Pemilihan Multirole Maritime Patrol Aircraft Anti Kapal Selam dan Anti Kapal Permukaan Sebagai Benchmark Industri Pertahanan Udara - Eko Yulianto; Tunggul Puliwarna; Jumino Jumino (Rekayasa, 2022)
The Indonesian Navy (TNI AL) is required to have a persistently broad Maritime Domain Awareness (MDA). In meeting its MDA demands, apart from using the KRI Radar, the Indonesian Navy needs to be supported by other airborne surveillance sensors and sensing satellites in outer space. For airborne sensors, Puspenerbal has been equipped with a fleet of maritime patrol aircraft Â (MPA) based on Casa NC 212-200 MPA and CN 235-220 MPA. However, all of these MPAs have a low detection capacity (less than 100 Km) and are not equipped with weapons to respond to threats on the surface or under the sea. For this reason, it is necessary to carry out research on the Long Range MPA requirement to support the tasks of the Navy with the aim of providing information and input to the Leaders in making decisions related to the plan to procure weapons and the strategic policies of the Navy to enforce defense and maintain security in the marine area of national jurisdiction. Indonesia This research will use the Analytical Hierarchy Process (AHP) method to determine the choice of maritime reconnaissance aircraft with predetermined criteria with alternative options, namely P-8A Poseidon, SAAB 6000 MPA, Kawasaki P-1, and ATR 72 MPA. The selected alternative was based on a combination of 3 criteria, namely P-8A Poseidon 58.3%, SAAB 6000 MPA 20.4%, Kawasaki P-1 14.4%, and ATR 72 MPA 6.8%. the result of the selection of the Tactical Reconnaissance Maritime Patrol Aircraft is that the P-8A Poseidon is the right alternative to choose. with an Inconsistency value of 0.06. This shows that the calculation of the alternative is still within the inconsistency threshold, which cannot be more than 0.1.